Paralytic dementia in a 6 year old girl - Krumdieck, Carlos F. (1935)
Clinical history of a girl of 6 years, heredosifilítica usually developed to 26 months presenting with dizziness character change and at 3 and a half years apopletiforme attack followed by a regressive type chart insane. Diagnosis between idiocy and dementia is discussed, establishing the demented nature of mental disorders. The possibility that epilepsy could have given these demonstrations are then studied, ruling out this hypothesis, to affirm the role played by hereditary syphilis, concluding by admitting, with reservations, the diagnosis of childhood paralytic dementia, relatively rare entity in childhood, but noted by various researchers.